2016
DOI: 10.3329/bsmmuj.v6i2.29130
|View full text |Cite
|
Sign up to set email alerts
|

Immunofluorescence pattern of antinuclear antibody and its association with autoantibody profile in systemic lupus erythematosus

Abstract: Abstract:Background: Antinuclear antibody (ANA) is useful in the diagnosis of systemic lupus erythematosus (SLE). Association

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
1
2
1
Order By: Relevance
“…In a previous Bangladeshi study also observed parallel result to the current study. [24] But in a Egyptian study, frequency of Anti ENA antibodies were found almost similar to present study except anti-RNP which was 10% in their study. [11] In our study, anti-RNP was more commonly associated with constitutional features including arthritis/arthralgia, malar rash, non-specific rash, photosensitivity and proteinuria.…”
Section: Discussionsupporting
confidence: 78%
“…In a previous Bangladeshi study also observed parallel result to the current study. [24] But in a Egyptian study, frequency of Anti ENA antibodies were found almost similar to present study except anti-RNP which was 10% in their study. [11] In our study, anti-RNP was more commonly associated with constitutional features including arthritis/arthralgia, malar rash, non-specific rash, photosensitivity and proteinuria.…”
Section: Discussionsupporting
confidence: 78%
“…Sharmin et al reported a sensitivity of 86.5% and Bentow et al reported a sensitivity of 81.5%. However, our results were higher than the reported 59% sensitivity of Karumanchi and Oommen [17][18][19].…”
Section: Discussioncontrasting
confidence: 95%
“…Speckled pattern (43.7%) followed by peripheral (34.3%) and homogenous pattern (21.8%) were present in their study. 15 Gonzalez and Rothdfield reported that the homogenous and peripheral patterns were found most frequently in SLE patients and only a few had speckled pattern. 23 Present study found homogenous (46.3%), speckled (17.6%), nucleolar (1.1%) and cytoplasmic (2.6%) staining pattern.Most of the literature reportedpresence of homogenous pattern in the majority of SLE cases.…”
Section: Resultsmentioning
confidence: 97%
“…7 Positive autoantibody titers at a dilution equal to or greater than 1:160 were usually considered as clinically significant. [15][16][17] Statistical analysis was done to assess the frequency of positivity, association of different patterns with different systemic involvement.…”
Section: Methodsmentioning
confidence: 99%